Tracking the emergence and usage of farmer led innovations (FLIs) in maize ecosystem: A pan India exploration - Priyajoy Kar
The study was carried out, by using case study method, to investigate the distinctive characteristics of a few selected farmer-led innovations (FLIs) in maize cropping systems created at the grassroots level across India. A total of five maize-based innovations produced at the grassroots level in various parts of India were purposefully chosen. The originality of these innovations is that they are based on the culture from which they originate and are based on local expertise. This study discovered that all farmer-led innovations generated by farmers were more useful than other existing options since these innovations were built with farmers' needs in mind. Furthermore, these were discovered to be and determined to be sustainable, owing to the fact that these inventions were produced using local resources and wisdom. All five innovations were discovered to be less expensive than alternative market-available technologies. The majority of selected technologies were determined to be profitable, with farmers benefiting after a specified period of hard labor and investment. All of the chosen technologies were discovered to be compatible with the needs of local farmers. The ideas generated by respondents were not commercialized due to several difficulties faced by the farmers to translate the innovations into marketable items, combined with the low demonstrability of these technologies.